Towards a theoretical framework for Integrated Team Leadership (IgTL). Issue 6 (1st November 2020) - Smith, Tony; Fowler Davis, Sally; Nancarrow, Susan; Ariss, Steven; Enderby, Pam
ABSTRACT: This study presents a framework for the leadership of integrated, interprofessional health, and social-care teams (IgTs) based on a previous literature review and a qualitative study. The theoretical framework for Integrated Team Leadership (IgTL) is based on contributions from 15 professional and nonprofessional staff, in 8 community teams in the United Kingdom. Participants shared their perceptions of IgT's good practice in relation to patient outcomes. There were two clear elements, Person-focused and Task-focused leadership behaviors with particular emphasis on the facilitation of shared professional practices. Person-focused leadership skills include: inspiring and motivating; walking the talk; change and innovation; consideration; empowerment, teambuilding and team maintenance; and emotional intelligence. Task-focused leadership behaviors included: setting team direction; managing performance; and managing external relationships. Team members felt that the IgTL should be: a Health or Social Care (HSC) professional; engaged in professional practice; and have worked in an IgT before leading one. Technical and cultural issues were identified that differentiate IgTL from usual leadership practice; in particular the ability to facilitate or create barriers to effective integrated teamworking within the organizational context. In common with other OECD countries, there are policy imperatives in England for further integration of health and social care, needed to improve the quality and effectiveness of care for older people with multiple conditions. Further attention is needed to support the development of effective IgTs and leadership will be a pre-requisite to achieve this vision. The research advances the understanding of the need for skilled interprofessional leadership practice.